Dengzhanxixin Injection Ameliorates Cognitive Impairment Through a Neuroprotective Mechanism Based on Mitochondrial Preservation in Patients With Acute Ischemic Stroke - An, Haiting; Tao, Wuhai; Liang, Ying; Li, Peng; Li, Min; Zhang, Xiaxia; Chen, Kewei; Wei, Dongfeng; Xie, Daojun; Zhang, Zhanjun (Frontiers in Pharmacology, 2021)
Acute ischemic stroke (AIS) is a global health burden and cognitive impairment is one of its most serious complication. Adequate interventions for AIS may have the potential to improve cognitive outcomes. In the present study, we selected Erigeron breviscapus (Vaniot) Hand.-Mazz. injection (Dengzhanxixin injection, DZXI), a widely used Chinese herbal injection, in contrast to edaravone as the positive control drug to test its potential to ameliorates neurological and cognitive impairments caused by AIS. We performed a two-week randomized trial with these two drugs in AIS patients presenting mild to moderate cognitive impairments. Neuropsychological tests and MRI examinations showed that DZXI attenuated the neurological and cognitive impairments of patients and protected the grey matter in specific regions from ischemic damage. Notably, DZXI exerted better effects than edaravone in some neuropsychological tests, probably due to the protective effect of DZXI on grey matter. To explore the therapeutic mechanisms, we carried out an experiment with a middle cerebral artery occlusion rat model. We found that DZXI decreased the infarct volume and increased the survival of neuronal cells in the ischemic penumbra; furthermore, DZXI modulated the mitochondrial respiratory chain process and preserved the mitochondrial structure in the brain tissue. Overall, our data suggested that the administration of DZXI is effective at ameliorating neurological and cognitive impairments in AIS, and the underlying mechanisms are related to the protective effects of DZXI on cerebral neurons and neuronal mitochondria.